Targeted therapies in triple-negative breast cancer - Marmé, Frederik; Schneeweiss, Andreas (Breast care, 2015)
Triple-negative breast cancer (TNBC) is a heterogeneous disease comprised of several biologically distinct subtypes. However, treatment is currently mainly relying on chemotherapy as there are no targeted therapies specifically approved for TNBC. Despite initial responses to chemotherapy, resistance frequently and rapidly develops and metastatic TNBC has a poor prognosis. New targeted approaches are, therefore, urgently needed. Currently, bevacizumab, a monoclonal anti-vascular endothelial growth factor (VEGF)-A antibody, is the only targeted agent with an approval for the therapy of metastatic breast cancer, but does not provide a specific benefit in the TNBC subtype. This review discusses the current clinical developments in targeted approaches for TNBC, including anti-angiogenic therapies, epidermal growth factor receptor (EGFR)-targeted therapies, poly(ADP-ribose) polymerase (PARP) inhibitors and platinum salts, as well as novel strategies using immune-checkpoint inhibitors, which have recently demonstrated first promising results. Strategies focusing on specific subtypes of TNBC like anti-androgenic therapies for the luminal androgen receptor subtype (LAR) and others are also discussed.